False transfixation of the liver using an endoscopic gastrostomy tube: Do not always believe in radiologic images - Gonçalo Nunes; Teresa Rodrigues Alves; Carlos Luz; Isabel Vieira; Luísa Carmona; Carla Adriana Santos; Jorge Fonseca (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Nunes G, Alves TR, Luz C, et al. False transfixation of the liver using a percutaneous endoscopy gastrostomy tube: Do not always believe in radiologic images. Turk J Gastroenterol 2017; 28: 526-7.